Design and Build Monitoring System for Pregnant Mothers and Newborns using the Waterfall Model - Purba, Ramen Antonov; Sondang, Sondang (Universitas Nusantara PGRI Kediri, 2022)
In Indonesia, the problems of pregnant women and newborns have not been resolved. The reason is that there is no monitoring system for pregnant women and newborns. This study aims to build a monitoring system for pregnant women and newborns. The monitoring system that will be made is mobile-based that can monitor and provide information about the health of pregnant women and children. The model used to create an information system uses the waterfall model. Meanwhile, to test the system built using the Blackbox test model. The plan that was created was tested directly to the user. As a result, the sequence in the waterfall model is proven to build a monitoring system for pregnant women and newborns. The black box model also showed if the built system did not have errors and was ready to be used. Combining the waterfall and BlackBox models results in a monitoring system for pregnant women and newborns whose entire menu can be used properly. The test was carried out on 25 pregnant women users, and it was found that the accumulated ratings were 89, 87, 88, and 89%. In this case, it is classified as Very Eligible.